Risk Factors Associated with the Occurrence of the Second-Litter Syndrome in Sows in Southeastern Mexico. (29th October 2013) - Segura Correa, José C.; Alzina-López, Alejandro; Santos-Ricalde, Ronald H.
Abstract : The objective was to estimate the incidence of and to determine the effect of some risk factors on the decrease of litter size at parity 2 of sows in three commercial farms in Yucatan, Mexico. Data on 8, 592 farrowing records of 4, 296 sows were analyzed using a binomial logistic regression procedure. The model included the fixed effect of farm (1, 2, and 3), year of farrowing (2003–2011), season of farrowing (dry, rainy, and windy), number of pigs born alive at first parity (<9, 9-10, 11-12, and >12 piglets), lactation length (<18, 18–24, and >24 days), and weaning to conception intervals (<4, 4–11, and >11 days). Fifty-five point eight percent of all sows presented a reduced or similar litter size at parity 2. The odds of decrease in the second litter size were 1.56 and 2.01 for farms 2 and 3, respectively. Higher odds were found for sows farrowing during the rainy and dry seasons (1.20 and 1.24, resp.) and for sows with large litters at parity 1 (>12 piglets, odds = 33.2). Sows with weaning to conception intervals <4 days and between 4 and 11 days had higher odds of a decrease in the second litter (1.78 and 2.74 pigs, resp.).